Answer:
x = -2/7
y = 8/7
Explanation:
1) Since the equations at the end are both equivalent to -2y:
-4x + 3y = -2y
x - 2 = -2y
2) We want to get y by itself:
-4x + 3y = -2y --> -4x = y
x - 2 = -2y --> -x/2 + 1 = y
3) Since both are equal to y, we can solve for x; set the equations equal to each other, then combine like terms via adding/subtracting/dividing/multiplying (in accordance to PEMDAS):
(-2) (-4x) = (-x/2 + 1) (-2)
8x = x - 2
(8x) -x = (x - 2) -x
7x = -2
(7x) / 7 = (-2) / 7
x = -2/7
4) Now that we know what x equals, substitute x with -2/7 in one of the initial equations:
x - 2 = -2y
-2/7 - 2 = -2y
5) Then, combine like terms via adding/subtracting/dividing/multiplying (in accordance to PEMDAS); then, simplify to get what y equals:
(-2/7 - 2) (-7) = (-2y) (-7)
2 + 14 = 14y
16 = 14y
(16) / 14 = (14y) / 14
16/14 = y
6) Simplify (reduce):
8/7 = y
7) Your final answer is:
x = -2/7, y = 8/7